2016
DOI: 10.1002/gps.4418
|View full text |Cite
|
Sign up to set email alerts
|

Are premorbid abnormal personality traits associated with behavioural and psychological symptoms in dementia?

Abstract: The presence of Clusters A (solitary/paranoid) and C (anxious/dependent) abnormal premorbid personality traits seems to affect the expression of certain behavioural and psychological symptoms in dementia, depression in particular. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Thus, some personality traits may favour, or on the contrary protect against, BPSD. Thus, in AD, increased neuroticism as a premorbid personality trait may be associated with a higher risk for depression, 1,65,68,69 and even be a risk factor for cognitive decline and AD. 70,71 Patients who have been suspicious or aggressive before dementia starts are more likely to have BPSD than those without these traits.…”
Section: Etiopathogenesis Of Bpsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some personality traits may favour, or on the contrary protect against, BPSD. Thus, in AD, increased neuroticism as a premorbid personality trait may be associated with a higher risk for depression, 1,65,68,69 and even be a risk factor for cognitive decline and AD. 70,71 Patients who have been suspicious or aggressive before dementia starts are more likely to have BPSD than those without these traits.…”
Section: Etiopathogenesis Of Bpsdmentioning
confidence: 99%
“…70,71 Patients who have been suspicious or aggressive before dementia starts are more likely to have BPSD than those without these traits. 1,69 However, such correlations have not always been found 68 and one of the more significant limitations of most of the studies currently available is the use of retrospective personality ratings, subjecting their findings to possible inaccuracies. Psychiatric diseases may be risk factors for dementia as this has been established for depression and for BPSD.…”
Section: Etiopathogenesis Of Bpsdmentioning
confidence: 99%
“…It is likely that these results reflect age bias in the criteria rather than any substantive relationship between pathological personality and cognitive decline. Another study found that informant reported premorbid Cluster A traits (paranoid, schizoid, and schizotypal PD) were associated with anxiety, depression and hallucinations in patients with a diagnosis of probable Alzheimer's disease, whereas Cluster C traits (avoidant, dependent, and obsessive-compulsive PD) were associated with depression [35]. Cluster B traits were associated specifically with symptoms of aggression and irritability.…”
Section: Later Life Outcomesmentioning
confidence: 99%
“…Certain premorbid personality traits, such as neuroticism, have been consistently shown to predict, or at least be associated with, specific BPSD, like depression (Low, Brodaty, & Draper, 2002;Sutin, Stephan, Luchetti, & Terracciano, 2017;Tabata et al, 2017). Prior et al (2016) also found premorbid personality traits to be associated with elevated levels of BPSD. Especially the presence of premorbid cluster A (solitary/paranoid) and C (anxious/dependent) personality traits is associated with agitation, psychosis, and depression in patients with dementia.…”
Section: Introductionmentioning
confidence: 90%